Studies on Patient Empowerment in Nursing in Türkiye: A Content Analysis of Postgraduate Theses - Şeyma Demir Erbaş; Elif Gençer Şendur (Akdeniz Hemşirelik Dergisi, 2026)
Aim Patient-centered care in healthcare requires patients to be more involved in decision-making processes and to have more control over their own health. This promotes patient empowerment initiatives. The purpose of this study is to examine postgraduate theses based on patient empowerment conducted in the field of nursing in Türkiye. Methods The study was conducted based on the descriptive content analysis of data obtained from postgraduate theses. The National Thesis Center database of the Council of Higher Education was searched between 01.07.2023 and 23.07.2024, and master’s and doctoral theses addressing patient empowerment by nurses were examined. Data analysis was reported in terms of publication year, purpose, type of thesis, research design, sample group and size, and type of experimental intervention. Results It was found that the majority of the postgraduate theses included in the research were doctoral theses conducted within the last five years. The master’s theses were conducted with cross-sectional design and methodological review, while the doctoral theses aimed to improve patient empowerment with an experimental intervention tool. The sample group consisted of individuals with chronic diseases, and the types of patient empowerment interventions included empowerment education, exercise intervention, creative drama, tele-nursing, and innovative clothing. Conclusion Patient empowerment studies in nursing have increased in recent years, particularly at the doctoral level, with a growing emphasis on intervention-based approaches. Expanding patient empowerment practices and conducting further experimental studies may contribute to improving health outcomes, especially among individuals with chronic diseases.